Therapeutic Effect of Curcumin Oral Gel on Salivary Epidermal Growth Factor and Lactate Dehydrogenase Levels in Relation to Oral Mucositis in Head and Neck Cancer Patients Undergoing Concurrent Chemoradiation - Rouaa S. Farhan; Fawaz D. Al-Aswad (Diyala Journal of Medicine, 2025)
Background: Curcumin is a traditional herbal medication, which has shown promise in a variety of pharmacologic applications. Epidermal growth factor an amino acid polypeptide found in saliva and other bodily fluids, which promotes cell proliferation and renewal. Lactate dehydrogenase is classified as altered protein markers present in saliva, and its levels showed significantly elevated in head and neck cancer. To study the effect of curcumin oral gel on levels of salivary epidermal growth factor and lactate dehydrogenase in head and neck cancer patients receiving concurrent chemoradiation induced oral mucositis. Patients and Methods: Ninety head and neck cancer patients receiving concurrent chemoradiation, 45 patients in each group. Saliva levels of lactate dehydrogenase and epidermal growth factor measured by an enzyme linked immunosorbent assay. WHO scale used to assess oral mucositis. Results: Highly significant increase in salivary epidermal growth factor and decrease in lactate dehydrogenase levels with less severe oral mucositis in group treated with curcumin. Significant differences were found between the two groups in the WHO scale at two weeks (P = 0.041) and six weeks (P=0.02). Conclusion: The current study concludes that curcumin oral gel can increase epidermal growth factor and reduce lactate dehydrogenase levels in saliva, and it may be used as an alternate treatment for oral mucositis-induced by chemoradiation. Keywords: Head and neck cancer, Curcumin, Oral mucositis.